Primary Care Physicians' Action Plans for Responding to Results of Screening Tests Based on the Concept of Quaternary Prevention - Jong-Myon Bae; Marc Jamoulle (Korean Society for Preventive Medicine, 2016)
Since noncommunicable diseases (NCDs) are generally controllable rather than curable, more emphasis is placed on prevention than on treatment. For the early detection of diseases, primary care physicians (PCPs), as well as general practitioners and family physicians, should interpret screening results accurately and provide screenees with appropriate information about prevention and treatment, including potential harms. The concept of quaternary prevention (QP), which was introduced by Jamoulle and Roland in 1995, has been applied to screening results. This article summarizes situations that PCPs encounter during screening tests according to the concept of QP, and suggests measures to face such situations. It is suggested that screening tests be customized to fit individual characteristics instead of being performed based on general guidelines. Since screening tests should not be carried out in some circumstances, further studies based on the concept of prevention levels proposed by Jamoulle and Roland are required for the development of strategies to prevent NCDs, including cancers. Thus, applying the concept of QP helps PCPs gain better insights into screening tests aimed at preventing NCDs and also helps improve the doctor-patient relationship by helping screenees understand medical uncertainties.